2019
DOI: 10.1155/2019/8965476
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, Mineral and Antinutrient Contents of Cocoyam (Xanthosoma sagittifolium (L.) Schott) from Ethiopia

Abstract: Cocoyam (Xanthosoma sagittifolium (L.) Schott) is an important food crop especially in the tropics and subtropics. Its cormels and leaves are eaten after cooking in the rural areas in Ethiopia. There is lack of information on the nutritional composition of cocoyam grown in the country. In this study, cormels of green- and purple- cocoyams were analyzed to determine proximate and mineral contents and antinutritional factors. The moisture contents (%) of green- and purple-cocoyams were 61.91 and 63.53, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Xanthosoma sagittifolium is very nutritious and highly productive and yet it's corms and cormels are being under utilized as energy feed resources (Onu et al, 2006, Owusu-Darko et al, 2014, Eyasu et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xanthosoma sagittifolium is very nutritious and highly productive and yet it's corms and cormels are being under utilized as energy feed resources (Onu et al, 2006, Owusu-Darko et al, 2014, Eyasu et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Cocoyam corms contains anti-nutritional factors such as tannins, hydrocyanid, oxalates, antitrypsin inhibitor (Okereke, 2012;Hand and Binh, 2013). The anti-nutritional factors in the cocoyam corms could be removed through drying, fermentation, cooking and toasting to make the product safe for human and livestock consumption (Ndimantang et al, 2006, Eyasu et al, 2019. Ndimantang et al (2006), Aboubakar et al (2008), Akinmutimi et al 2006), Chandra Subhash et al (2012 observed that Xanthosoma sagittifolium corm meal proved to serve as good food for both man and livestock with its appreciable nutritional profile and higher productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral composition was determined in each diluted ash using spectrophotometry and titrimetry methods following Wada et al, (2019). Zinc (Zn), iron (Fe), phosphorus (P) and iodine (I) were determined by molecular Absorption using DR 2800 spectrophotometer, while Ca 2+ and Mg 2+ were determined by titrimetry using the Digital burette and EDTA method (Tegegne et al, 2020).…”
Section: Mineral Composition Analysismentioning
confidence: 99%
“…It also contains other anti-nutritional and toxic properties such as phytate and tannin which cause health hazard for humans and poultry if not well processed (Sefa-Dedeh and Agyir-Sackey, 2004). Eyasu et al (2019), in a study with Xanthosoma sagittifolium, observed that the proximate, mineral and anti-nutrients content of the green and purple varieties of Xanthosoma sagittifolium (L.) Schott were as follows, 61.91 and 63.53% moisture contents, crude protein (10.10%) and (8.48%), fibre, 2.66% and 2.14%, fat contents 0.85 and 0.22% respectively for green and purple varieties of Xanthosoma sagittifolium respectively. However, they also observed carbohydrate and gross energy values (Kcal/100g) of green and purple Xanthosoma sagittifolium to be 85.36% and 378.47Kcal/100g and 84.76% and 380.27Kcal/100g, ash contents, 3.25 and 2.27% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, they also observed carbohydrate and gross energy values (Kcal/100g) of green and purple Xanthosoma sagittifolium to be 85.36% and 378.47Kcal/100g and 84.76% and 380.27Kcal/100g, ash contents, 3.25 and 2.27% respectively. Eyasu et al (2019), also observed that aroids are group with the neglected and under-utilized crops which over the years have received little research attention. However, they are important tuberous root crops that play significant role in the livelihood of millions of relatively poor people in developing countries.…”
Section: Introductionmentioning
confidence: 99%